2010
DOI: 10.1002/hbm.20942
|View full text |Cite
|
Sign up to set email alerts
|

Group‐level variations in motor representation areas of thenar and anterior tibial muscles: Navigated Transcranial Magnetic Stimulation Study

Abstract: Navigated transcranial magnetic stimulation (TMS) can be used to stimulate functional cortical areas at precise anatomical location to induce measurable responses. The stimulation has commonly been focused on anatomically predefined motor areas: TMS of that area elicits a measurable muscle response, the motor evoked potential. In clinical pathologies, however, the well-known homunculus somatotopy theory may not be straightforward, and the representation area of the muscle is not fixed. Traditionally, the anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 44 publications
5
41
0
Order By: Relevance
“…A few studies have estimated the approximate locations of the TA hotspot to be within 1–3 cm lateral to the vertex [2,17]. In a previous study using image guided TMS, Niskanen et al [22] reported that optimal stimulation site for the TA muscle was near the longitudinal fissure for healthy individuals, and that the observed variance in the location did not correlate with age or head circumference. In our study, we confirmed the optimal stimulation location using standard TMS, and furthermore, we reported the precise location in the anteroposterior and mediolateral coordinates on the skull.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have estimated the approximate locations of the TA hotspot to be within 1–3 cm lateral to the vertex [2,17]. In a previous study using image guided TMS, Niskanen et al [22] reported that optimal stimulation site for the TA muscle was near the longitudinal fissure for healthy individuals, and that the observed variance in the location did not correlate with age or head circumference. In our study, we confirmed the optimal stimulation location using standard TMS, and furthermore, we reported the precise location in the anteroposterior and mediolateral coordinates on the skull.…”
Section: Discussionmentioning
confidence: 99%
“…[36] TMS pulses were delivered within the bounds with special attention paid to regions surrounding the hotspot territory. [37] For each stimulation point MEPs were calculated as the peak-to-peak amplitude of the filtered (2nd order Butterworth filter, 5–250 Hz band-pass) EMG signal 20–50 ms after the TMS pulse. MEP amplitudes were interpolated to a 10 × 10 cm mesh of 5 mm resolution centered on the M1 hotspot, using cubic surface interpolation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the reference electrode was placed at the elbow. Then, a coarse round of single-pulse stimulations was conducted to localize the spot with the highest MEP amplitude, the motor hotspot, which is usually found within the area of the hand knob [14]. During pulse application, the induced electrical field was oriented perpendicular to the precentral gyrus, and the RMT was then determined at the motor hotspot.…”
Section: Methodsmentioning
confidence: 99%